Corporate Internet Reporting as a Mediator Between Corporate Governance and Firm Value: Evidence from Sri Lanka - Krishnasamy Tharsika; Puwanenthiren , Pratheepkanth; Nuradhi K. Jayasiri (Indonesian Management and Accounting Research, 2026)
This study investigates how corporate governance characteristics—specifically board attributes and audit committee attributes—affect firm value, with Corporate Internet Reporting (CIR) examined as a mediating mechanism among listed non-financial companies in Sri Lanka. Using a quantitative, deductive approach, the study analyzes cross sectional secondary data from 97 firms for the 2022/23 period, obtained from annual reports and corporate websites. Partial Least Squares Structural Equation Modeling (PLS SEM) is employed to assess the relationships among governance mechanisms, CIR disclosure, and firm value measured by Tobin’s Q. The results show that board characteristics exert a significant positive effect on both CIR practices and firm value, with CIR partially mediating the relationship between board characteristics and firm value. In contrast, audit committee attributes do not significantly influence CIR or firm value, and no mediating effect is observed. The study contributes to the literature by empirically validating CIR as a governance driven signaling mechanism in an emerging market context and provides practical insights for regulators and corporate leaders seeking to strengthen board effectiveness, enhance transparency, and improve investor confidence